Stemless Humeral Prosthesisin Shoulder Arthroplasty:Systematic Review - Silva, Rómulo (2024)
Introduction: Stemless shoulder prostheses were introduced as a new shoulder replacement system designed to reduce the potential risks associated with the humeral component and achieve better functional results by lowering the surgical complication rates. This systematic review aims to assess the latest available published findings regarding stemless shoulder replacement. Methods: A search in PubMed, Scopus, and Clarivate Web of Science databases was performed, selecting publications that reported the constant score for functional assessment in patients submitted to shoulder arthroplasty with a stem less prosthesis. Results: Three types of shoulder arthroplasties were identified, with a constant score average between 63.4% and 73.3% and with a revision rate average between 2.8% and 3.4%. These results were similar among studies with differ ent followup duration: 6 months to 9 years. Conclusion: Shoulder arthroplasty with stemless prosthesis is very promising with favourable results in the short and mediumterms regarding improvement in the shoulder function, pain relief and patient satisfaction and low rates of complications.